Le pioniere dell’Arte: Barbara Flaminia e Vincenza Armani - Simoncini, Francesca (Drammaturgia, 2020)
The section is devoted to the biographical profiles of Vincenza Armani (1530 ca.-1569) and Barbara Flaminia (1562-post 1584).